The Impact of Tourism Investment on Enhancing Tourism Demand in Iraq: A Benchmarking Study for the Period (2018-2024) - Auday Sabeeh Lazim (Indonesian Journal of Education Methods Development, 2026)
General Background: Tourism has increasingly been recognized as a strategic sector for economic diversification, particularly in economies seeking alternatives to dependence on a single source of income. Specific Background: Iraq possesses diverse tourism resources; however, tourism investment levels remain relatively modest despite the sector’s development potential. Knowledge Gap: Limited evidence exists regarding the relationship between tourism investment, infrastructure development, macroeconomic stability, and tourism demand in Iraq during periods characterized by structural and external shocks. Aims: This study aims to examine the correlation between tourism investment and inbound tourism demand in Iraq during the period 2018–2024 and to identify the development gap between tourism resources and actual investment performance. Results: Using a quantitative analytical approach and a multiple regression model, the study found a significant positive relationship between tourism investment and tourism demand. Tourism demand exhibited low elasticity toward traditional investments but responded more strongly to high-quality investments. The findings also indicate that stability is the most influential factor affecting tourism demand and investment incentives. Novelty: The study incorporates a stability indicator to isolate the effects of crises and instability within the tourism demand model. Implications: The findings suggest that improving investment quality, strengthening infrastructure, and maintaining political and economic stability are essential for supporting sustainable tourism demand growth and tourism sector development in Iraq. Keywords: Tourism Investment, Tourism Demand, Infrastructure Development, Economic Stability, Iraq Key Findings HighlightsTourism demand responded more strongly to qualitative investment than conventional investment patterns.Positive statistical association was identified between capital allocation and visitor arrivals.Security and economic conditions emerged as the dominant determinant of sector performance.